Lighting "Paradise": A Sociopolitical History of Electrification in Bali. Issue 1 (1st March 2017) - Mohsin, Anto
Abstract : The article explores the sociopolitical history of electrification in Bali in the so-called New Order period of Indonesia (1966–98). It discusses the intertwining factors that drove electrification on the island to move more quickly than in other areas in Indonesia, culminating in the electrification of all Bali's villages in 1995. Bali's tourism industry, the New Order's village electrification program, the construction a national television network, and Bali's selection as a venue of many important regional and international meetings in Indonesia all contributed to the rapid growth rate of electrification on the island. Underlying all these factors was the New Order regime's construction and projection to the world of Indonesia's identity as a rapidly modernizing nation with a part to play on the global stage. The New Order government thus poured a huge amount of resources into electrifying the island. Although the Balinese welcomed the attention and resources provided by the Suharto government to develop Bali, they wanted to ensure this effort was not merely to use the island to promote Indonesia's image overseas. Rather, they wanted development there to be more meaningful than it was and to improve people's welfare. Their criticisms shared the same sentiments of some critiques of New Order Indonesia's development efforts in general.